2019
DOI: 10.24050/reia.v16i31.1230
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Motivation and Improving Student Performance in an introductory programming course: An Integrated Teaching Approach

Abstract: This paper expands a teaching proposal presented at the Innovation and Technology in Computer Science Education Conference, in 2016.  The proposal provides an integrated teaching approach for improving students’ performance in a first programming course. The approach is based on four main components: the use of Python as first programming language, project-oriented and problem-based learning, multimedia resources, and assessment rubrics. Material and learning resources for the course development are av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…However, they tend to follow syntax-oriented programming teaching approaches, without focusing on computational thinking, with few connections to mathematics and science [19]. Furthermore, in the work of [18], they indicate that the Python programming language is suitable for introductory programming courses because of its simple syntax and ease for code debugging, they also point out that it is necessary to consider other aspects such as pedagogical strategies that allow improving the programming teaching-learning process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they tend to follow syntax-oriented programming teaching approaches, without focusing on computational thinking, with few connections to mathematics and science [19]. Furthermore, in the work of [18], they indicate that the Python programming language is suitable for introductory programming courses because of its simple syntax and ease for code debugging, they also point out that it is necessary to consider other aspects such as pedagogical strategies that allow improving the programming teaching-learning process.…”
Section: Discussionmentioning
confidence: 99%
“…In [18], they present a teaching approach based on four components: The use of the Python programming language, project-oriented and problem-based learning methodologies, multimedia resources available on virtual platforms, and evaluation rubrics. The approach used improved the academic performance of the students, which is evidenced in the grades obtained, and the dropout rates were reduced.…”
Section: Related Workmentioning
confidence: 99%
“…Collaborative Learning (CSCL) approach integrates artificial intelligence (AI) to improve the learning process through collaboration and information and communication technology (ICT) (Kozma, 2000, Loizzo & Ertmer, 2016, Docq & Daele, 2001, Solarte-Pabón & Machuca-Villegas, 2019, Thomas et al, 2002. According to Magnisalis et al, 2011, the CSCL approach is based on the following processes: a)…”
Section: Introductionmentioning
confidence: 99%
“…In addition, learning programming may result in resistance to learn among non-information or non-computer majors when their learning experiences and performances are worse than those of computer science majors [ 25 ]. It is reported that programming courses typically have a large number of students who fail or drop out, whether computer science majors or not [ 104 ]. Many students regard programming courses as difficult and lowly motivating [ 2 , 3 , 14 , 59 , 104 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that programming courses typically have a large number of students who fail or drop out, whether computer science majors or not [ 104 ]. Many students regard programming courses as difficult and lowly motivating [ 2 , 3 , 14 , 59 , 104 ]. It is mentioned that the two key reasons for students’ high failure rates in programming courses are teaching methods and curriculum organization [ 106 ].…”
Section: Introductionmentioning
confidence: 99%